Biomechanical analysis of the placement of fixation lag screw in different intertrochanteric hip fracture angles. Issue 2 (7th June 2019) - Choh, Alex C.T.; Chong, Desmond Y.R.
Abstract : The common surgical method for fracture fixation in the femoral neck and intertrochanteric region is the implantation a dynamic lag screw into the femoral head. However, failure rates of this fixation are high due to a cut‐out of the lag screw from the femoral head. It is unclear if the lag screw positions will affect the stabilisation of the intertrochanteric fracture with different fracture angles. This study aimed to examine the influence of lag screw placement in the fixation of hip fractures with different fracture angles in healthy and osteoporotic femurs using three‐dimensional finite element analysis. Two screw positions at the centre and inferior–posterior (IP) of the femoral head with three fracture angles (30°, 45°, 60°) were studied. The results showed that varying fracture angles and the onset of disease (osteoporosis) have influenced the optimal placement of the lag screw. The lag screw in the IP position in the healthy femur with 30° and 45° fracture angles and osteoporotic femur with 30° fracture angle induced lower periprosthetic bone strains. For a healthy femur with 60° fracture angle and osteoporotic bone with 45° and 60° fracture angles, a centralised placement of the lag screw in the femoral neck was preferred.